2015
DOI: 10.1001/jamainternmed.2014.6573
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis Use Among Patients Requiring Interhospital Transfer for ST-Segment Elevation Myocardial Infarction Care

Abstract: IMPORTANCE Guidelines for patients with ST-segment elevation myocardial infarction (STEMI) recommend timely reperfusion with primary percutaneous coronary intervention (pPCI) or fibrinolysis. Among patients with STEMI who require interhospital transfer, it is unclear how reperfusion strategy selection and outcomes vary with interhospital drive times. OBJECTIVE To assess the association of estimated interhospital drive times with reperfusion strategy selection among transferred patients with STEMI in the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 30 publications
3
49
0
3
Order By: Relevance
“…Some of the examples of systems of care for heart attack are the Mission: Lifeline STEMI system of care promulgated by the American Heart Association (http://maps.heart.org/ml/#;); and the RACE (Regional Approach to Cardiovascular Emergencies (https://racecars.dcri.duke.edu/) project utilized by the Carolinas Healthcare System. Additionally, a recent report from the National Cardiovascular Data Registry showed that the median interhospital driving time was 57 minutes (IQR 36–88 minutes) in the United States 20. The interhospital driving times suggest that fibrinolytic therapy should be considered for some of these patients, as supported by the Mission: Lifeline and RACE protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the examples of systems of care for heart attack are the Mission: Lifeline STEMI system of care promulgated by the American Heart Association (http://maps.heart.org/ml/#;); and the RACE (Regional Approach to Cardiovascular Emergencies (https://racecars.dcri.duke.edu/) project utilized by the Carolinas Healthcare System. Additionally, a recent report from the National Cardiovascular Data Registry showed that the median interhospital driving time was 57 minutes (IQR 36–88 minutes) in the United States 20. The interhospital driving times suggest that fibrinolytic therapy should be considered for some of these patients, as supported by the Mission: Lifeline and RACE protocols.…”
Section: Discussionmentioning
confidence: 99%
“…An observational study using the Acute Coronary Treatment and Intervention Outcomes Network Registry-Get With the Guidelines database between 2008 and 2012 21 showed that only 51.3% of patients with STEMI (≤12 hours) transferred for PPCI achieved the FMCto-balloon time of ≤120 minutes and 34.3% of fibrinolysis-eligible patients received pretransfer fibrinolysis with only 43.8% achieving a door-to-needle time of ≤30 minutes. Similarly, in the present study, only 45.8% of patients (26.1% of transferred patients) in the PPCI group achieved the FMC-to-balloon time of ≤120 minutes, even though the median door-to-balloon time at STEMI-receiving hospitals (80 minutes) was within the recommended 90 minutes.…”
Section: Sim Et Al Pharmacoinvasive Strategy In St-elevation Myocardimentioning
confidence: 99%
“…24 An alternative interpretation is that focused improvement is required in use of prehospital activation and transfer to higher volume PCI centers to achieve guideline mandated primary PCI practice.…”
Section: Mode and Time Of Transfermentioning
confidence: 99%